Does distance matter? Embodiment and perception of personalized avatars in relation to the self-observation distance in virtual reality - Wolf, Erik; Döllinger, Nina; Mal, David; Wenninger, Stephan; Bartl, Andrea; Botsch, Mario; Latoschik, Marc Erich; Wienrich, Carolin (Frontiers in Virtual Reality, 2022)
Virtual reality applications employing avatar embodiment typically use virtual mirrors to allow users to perceive their digital selves not only from a first-person perspective but also from a holistic third-person view. However, due to distance-related biases such as the distance compression effect or a reduced relative rendering resolution, the self-observation distance (SOD) between the user and the virtual mirror might influence how users perceive their embodied avatar. Our article systematically investigates the effects of a short (1 meter), middle (2.5 meter), and far (4 meter) SOD between user and mirror on the perception of personalized and self-embodied avatars. The avatars were photorealistic reconstructed using state-of-the-art photogrammetric methods. Thirty participants were repeatedly exposed to their real-time animated self-embodied avatars in each of the three SOD conditions. In each condition, the personalized avatars were repeatedly altered in their body weight, and participants were asked to judge the (1) sense of embodiment, (2) body weight perception, and (3) affective appraisal towards their avatar. We found that the different SODs are unlikely to influence any of our measures except for the perceived body weight estimation difficulty. Here, the participants judged the difficulty significantly higher for the farthest SOD. We further found that the participants' self-esteem significantly impacted their ability to modify their avatar's body weight to their current body weight and that it positively correlated with the perceived attractiveness of the avatar. Additionally, the participants' concerns about their body shape affected how eerie they perceived their avatars. Both measures influenced the perceived body weight estimation difficulty. For practical application, we conclude that the virtual mirror in embodiment scenarios can be freely placed and varied at a distance of one to four meters from the user without expecting major effects on the perception of the avatar.